Validity Test of The Acupressure Model Integrated Spiritual Coping Skill as an Effort to Reduce Anxiety Level in Chronic Kidney Disease - Supriyadi Supriyadi (Genius Journal, 2022)
Objective: Collecting information and testing validation for the design of an acupressure model integrated with spiritual coping skills as an effort to reduce anxiety levels in patients with chronic kidney disease proves that acupressure intervention integrated with spiritual coping skills has an effect on anxiety levels in CKD patients with hemodialysis through improving serotonin levels, and IgG Method: This study uses Research and Development (R&D), the stages carried out in this study were stages one, two and three, namely: information gathering, product/model design, expert validation and revision. Samples were taken by purposive sampling technique, grouped into two, the first group was a sample of the information gathering stage, totaling 10, the second group was a sample of the expert validation stage, totaling 9 people consisting of specialist doctors, psychologists and religious leaders. Information collection data was tested using qualitative discriminatory and expert validation data was tested with intraclass correlation coefficient Results: The results of gathering information concluded that the impact of hemodialysis treatment is the emergence of stress and anxiety in patients, anxiety, data can be overcome by acupressure treatment supported by activities that can meet psychological and religious/spiritual needs, thus providing a sense of comfort and increasing faith. Acupressure action with religious coping can reduce anxiety. Expert validation showed that the eligibility score was 90.9% with p=0.001 meaning that acupressure integrated spiritual coping skills was feasible as a model for reducing anxiety levels in patients with chronic kidney disease in the very feasible category. Conclusion: The application of acupressure model integrated spiritual coping skills is feasible as a model to reduce anxiety levels in patients with chronic kidney disease on hemodialysis